2014
DOI: 10.1038/npp.2014.91
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Trace Amine-Associated Receptor 1 Agonist RO5263397 on Abuse-Related Effects of Cocaine in Rats

Abstract: Animal knockout studies suggest that trace amine-associated receptor (TAAR) 1 is involved in behavioral effects of psychostimulants such as cocaine. Recently, several highly selective TAAR 1 agonists have been discovered. However, little is known of the impact of TAAR 1 agonists on abuse-related effects of cocaine. Here, we report the effects of a TAAR 1 agonist RO5263397 on several abuse-related behavioral effects of cocaine in rats. RO5263397 was evaluated for its effects on cocaine-induced behavioral sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 37 publications
16
91
0
Order By: Relevance
“…Both full and partial TAAR1 agonists are known to be effective in reversing hyperactivity in pharmacologic or genetic models of hyperdopaminergia and NMDA deficiency in mice (Revel et al, 2012;Revel et al, 2013). Interestingly, TAAR1-KO mice are more prone to the addictive properties of methamphetamine, ethanol, and MDMA (Di Cara et al, 2011;Achat-Mendes et al, 2012;Lynch et al, 2013), while recent reports from different groups have demonstrated that TAAR1 full and partial agonists reduce cocaine-conditioned place preference, self-administration, and relapse (Revel et al, 2012;Pei et al, 2014;Thorn et al, 2014a;Thorn et al, 2014b). As impulsivity is considered to be a specific trait in the pathophysiology of drug addiction, it is possible that TAAR1 can reduce addictive behaviors in part through PFC-related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Both full and partial TAAR1 agonists are known to be effective in reversing hyperactivity in pharmacologic or genetic models of hyperdopaminergia and NMDA deficiency in mice (Revel et al, 2012;Revel et al, 2013). Interestingly, TAAR1-KO mice are more prone to the addictive properties of methamphetamine, ethanol, and MDMA (Di Cara et al, 2011;Achat-Mendes et al, 2012;Lynch et al, 2013), while recent reports from different groups have demonstrated that TAAR1 full and partial agonists reduce cocaine-conditioned place preference, self-administration, and relapse (Revel et al, 2012;Pei et al, 2014;Thorn et al, 2014a;Thorn et al, 2014b). As impulsivity is considered to be a specific trait in the pathophysiology of drug addiction, it is possible that TAAR1 can reduce addictive behaviors in part through PFC-related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, TAAR1 agonists appear to have a similar beneficial anticraving effect in all such instances (Tables 6 and 8). Responses to cocaine (which itself is not a ligand for TAAR1), as well as drugtaking behaviors induced by its administration, are modified by TAAR1 agonists such that agonist-induced decreases in cocaine CPP (Thorn et al, 2014a), both cueand drug-primed reinstatement (Pei et al, 2014;Thorn et al, 2014a), hyperactivity (Revel et al, 2011(Revel et al, , 2013, reward memory , self-administration , sensitization (Thorn et al, 2014a,b), and withdrawal-induced drug seeking (Pei et al, 2014) have all been reported. Furthermore, TAAR1 activation causes a downward shift in dose-response curves for cocaine reward efficacy, confirming lesser rewarding properties.…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 99%
“…Thus, while when administered prior to cocaine conditioning, TAAR1 agonist did not modify the development of the CPP, it could reduce the expression of the already established CPP when administered prior to the test session. Also in a model of cocaine relapse, the cocaine-primed reinstatement of cocaine seeking, TAAR1 activation reduced the relapse of the cocaine-seeking behavior [12]. Altogether, these data indicate that TAAR1 activation reduces the sensitizing, rewarding, and reinforcing effects of cocaine and TAAR1 should be explored further as a potential target for the treatment of cocaine addiction.…”
Section: Role Of Taar1 In Addictionmentioning
confidence: 71%
“…Regarding the mechanism of action, it is shown that TAAR1 activation reduces the dopamine release induced by cocaine, as measured by FCSV in the nucleus accumbens, without altering the DAT functions, suggesting an involvement of other mechanisms than direct interference with dopamine uptake such as the alteration of D2 receptors activity [7]. In another study, TAAR1 partial agonist has been used to reduce several cocaine-mediated behaviors [12,84]. First, TAAR1 agonist administration reduced the expression of cocaine behavioral sensitization.…”
Section: Role Of Taar1 In Addictionmentioning
confidence: 98%
See 1 more Smart Citation